Isolation and in silico characterization of cinnamate 4-hydroxylase (C4H) gene controlling the early stage of phenylpropanoid biosynthetic pathway in Kelampayan (Neolamarckia cadamba, Rubiaceae) developing xylem tissues - Tchin, Boon Ling; Ho Wei, Seng; Pang, Shek-Ling (Asian Journal of Agriculture and Biology, 2018)
Cinnamate 4-hydroxylase (C4H) is one of the enzymes involved at the starting point of the phenylpropanoid and lignin biosynthesis pathway. It involves in the hydroxylation of cinnamate to 4-coumarate. In this paper, we isolated and in silico characterized the complete sequence of cinnamate 4-hydroxylase (C4H) gene from Neolamarckia cadamba in Malaysia. The C4H singletons obtained from the NcdbEST were used to predict the hypothetical full-length of NcC4H through the contig mapping approach. RT-PCR was used to amplify the full-length C4H cDNA clone and subsequently the PCR amplicons were sequenced and analysed. The NcC4H cDNA was 1,651 bp long with a 505 amino acid sequence, a 18 bp 5’-UTR and a 115 bp 3’-UTR. The predicted NcC4H protein contains P450-featured motifs. These include the heme-binding domain, a threonine-containing binding pocket motif and the proline-rich region. Peptide sequence comparison and phylogenetic analyses revealed that NcC4H was clustered with class I C4H instead of class II C4H, which is preferentially involved in phenylpropanoid and lignin biosynthesis pathway. This full-length NcC4H cDNA can be used for developing genetic marker to identify economic trait loci (ETL) for wood quality traits via genomics-assisted selection (GAS) or candidate gene mapping approach.